Resistance to echinocandin antifungal agents in the United Kingdom in clinical isolates of Candida glabrata: Fifteen years of interpretation and assessment. (21st May 2019) - Fraser, Mark; Borman, Andrew M; Thorn, Robin; Lawrance, Lynne M
Abstract: Candidemia is widely reported as the fourth most common form of bloodstream infection worldwide. Reports of breakthrough cases of candidemia are increasing, especially in the context of a move away from azole antifungals as prophylactic or first line treatment toward the use of echinocandin agents. The global evaluation of echinocandin antifungal susceptibility since 2003 has included switches in testing methodologies and the move to a sentinel echinocandin approach for classification reporting. This study compiles previously unpublished data from echinocandin susceptibility testing of UK clinical isolates of C. glabrata received at the Public Health England Mycology Reference Laboratory from 2003 to 2016 and reevaluates the prevalence of resistance in light of currently accepted testing protocols. From 2015 onward, FKS gene mutation detection using a novel Pyrosequencing® assay was assessed as a predictor of echinocandin resistance alongside conventional susceptibility testing. Overall, our data show that echinocandin resistance in UK isolates of C. glabrata is a rare phenomenon and prevalence has not appreciably increased in the last 14 years. The pyrosequencing assay was able to successfully detect hot spot mutations in FKS1 and FKS2, although not all isolates that exhibited phenotypic resistance demonstrated detectable hot spot mutations. We propose that a rapid genomic based detection method for FKS mutations, as part of a multifactorial approach to susceptibility testing, could help provide accurate and timely management decisions especially in regions where echinocandin resistance has been reported to be emerging in this important pathogen.